2021
DOI: 10.3390/rs13183762
|View full text |Cite
|
Sign up to set email alerts
|

Landscape Structure and Seasonality: Effects on Wildlife Species Richness and Occupancy in a Fragmented Dry Forest in Coastal Ecuador

Abstract: Despite high fragmentation and deforestation, little is known about wildlife species richness and occurrence probabilities in tropical dry forest (TDF) landscapes. To fill this gap in knowledge, we used a Sentinel-2-derived land-cover map, Normalized Difference Vegetation Index (NDVI) data and a multi-species occupancy model to correct for detectability to assess the effect of landscape characteristics on medium and large mammal occurrence and richness in three TDF areas that differ in disturbance and seasonal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…While it is known that the species' daily activity pattern responds to changes in abiotic conditions and varies with age, these responses have predominantly been studied in temperate ecosystems. Despite the species' high occupancy in SDTF (Haro-Carrión et al 2021), their daily activity patterns have not been thoroughly evaluated (but see Sánchez-Rojas et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…While it is known that the species' daily activity pattern responds to changes in abiotic conditions and varies with age, these responses have predominantly been studied in temperate ecosystems. Despite the species' high occupancy in SDTF (Haro-Carrión et al 2021), their daily activity patterns have not been thoroughly evaluated (but see Sánchez-Rojas et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…3). This pattern can be related to changes across space and time that generates a greater heterogeneity of micro-habitats inside a small forest fragment (Basset et al, 2015;Haro-Carrión et al, 2021;Valenzuela & Macdonald, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…This could be crucial in small fragments (< 30 ha) where opportunities to find food, water, and suitable shelters are limited, especially for large-sized mammals (Crooks 2002;Crooks et al, 2017;Morera et al, 2021). For instance, Ocelots (Leopardus pardalis), Greater Grison (Galictis vittata) and Collared Peccaries (Pecari tajacu) expand their home ranges during the dry season (Dillon & Kelly, 2008;Haro-Carrión et al, 2021).…”
Section: Palabras Clavementioning
confidence: 99%
“…A quarter of extant species are threatened and the risk of extinction has increased dramatically (Johnson et al., 2017; Turvey & Crees, 2019) in the last 40 years (Di Minin et al., 2016). However, recent studies have shown that many mammals differ in their level of sensitivity to anthropogenic (Haro‐Carrión et al., 2021; Rios et al., 2022) and seasonal changes (Cruz et al., 2018; Dias et al., 2019; Haro‐Carrión et al., 2021; Miles et al., 2006; Penido et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Seasonal dry forests are among the most threatened ecosystems in the world due to the fast expansion of anthropogenic activities and vulnerability to climate change (de Oliveira et al., 2012; Haro‐Carrión et al., 2021; Miles et al., 2006). The Brazilian Caatinga is one of the largest and most biodiverse seasonal dry tropical forests in the Americas (Neri et al., 2019), and it is the Brazilian ecosystem most vulnerable to the desertification process (Costa‐Pinto et al., 2023).…”
Section: Introductionmentioning
confidence: 99%